Relationship of Parity, Knowledge and Anemia Status with Perineal Wound Healing in Postpartum Mothers at PMB Bukit Sangkal Palembang Working Area in 2021 - Rosi Ratna Sari; Satra Yunola; Helni Anggraini (Institute of Computer Science (IOCS), 2022)
Background: The impact of improper perineal wound care can cause infection and hinder the perineal wound healing process. The appearance of infection in the perineum can spread to the urinary tract or in the birth canal which can cause complications of bladder infection or infection of the birth canal. Based on the results of a preliminary study conducted by researchers at the PMB working area of ​​the Bukit Sangkal Public Health Center, Palembang City, the number of cases of childbirth in 2020 was obtained as many as 345 cases, 215 cases of deliveries with perineal sutures and 48 cases of wet perineal sutures during post-pastum follow-up visits today. eighth. The purpose of this study was to determine the relationship between parity, knowledge and anemia status with perineal wound healing in postpartum women at PMB Bukit Sangkal Palembang Working Area in 2021. This study used a quantitative method with a